Can Weakness in End-Range Plantar Flexion After Achilles Tendon Repair Be Prevented?. Issue 5 (17th May 2018) - Orishimo, Karl F.; Schwartz-Balle, Sidse; Tyler, Timothy F.; McHugh, Malachy P.; Bedford, Benjamin B.; Lee, Steven J.; Nicholas, Stephen J.
Background: Disproportionate end-range plantar flexion weakness, decreased passive stiffness, and inability to perform a heel rise on a decline after Achilles tendon repair are thought to reflect increased tendon compliance or tendon lengthening. Since this was first noted, we have performed stronger repairs and avoided stretching into dorsiflexion for the first 12 weeks after surgery. Hypothesis: Using stronger repairs and avoiding stretching into dorsiflexion would eliminate end-range plantar flexion weakness and normalize passive stiffness. Study Design: Case series; Level of evidence, 4. Methods: Achilles repairs with epitendinous augmentation were performed on 18 patients. Plantar flexion torque, dorsiflexion range of motion (ROM), passive joint stiffness, and standing single-legged heel rise on a decline were assessed at 43 ± 24 months after surgery (range, 9 months to 8 years). Maximum isometric plantar flexion torque was measured at 20° and 10° of dorsiflexion, neutral position, and 10° and 20° of plantar flexion. Passive dorsiflexion ROM was measured with a goniometer. Passive joint stiffness was computed from the increase in passive torque from 10° to 20° of dorsiflexion. Tendon thickness was measured by use of digital calipers. Plantar flexion electromyographic (EMG) data were recorded during strength and functional tests. Analysis of variance and chi-square tests were used to assess weakness and function. Results: Marked weakness was evident on the involved side at 20° of plantar flexion (deficit, 26% ± 18%; P < .001), with no weakness at 20° of dorsiflexion (deficit, 6% ± 17%; P = .390). Dorsiflexion ROM was decreased 5.5° ± 8° ( P = .015), and tendon width was 8 ± 3 mm greater on the involved side ( P < .001). Passive joint stiffness was similar between the involved and noninvolved sides. Only 2 of 18 patients could perform a decline heel rise on the involved side compared with 18 of 18 on the noninvolved side ( P = .01). No difference in EMG amplitude was found between the involved and noninvolved sides during the strength or heel rise tests. Conclusion: The use of stronger repair techniques and attempts to limit tendon elongation by avoiding dorsiflexion stretching did not eliminate weakness in end-range plantar flexion. EMG data confirmed that end-range weakness was not due to neural inhibition. Physiological changes that alter the force transmission capability of the healing tendon may be responsible for this continued impairment. This weakness has implications for high-demand jumping and sprinting after Achilles tendon repair.